PENGARUH KOMPETENSI, BUDAYA KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Ali Brahamsar Nasution; Hasnah Harahap; Indra Arya; Sagiono .; Agus Salim (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Problem of this study how influence of competency on performance. How influence of job culture on performance. How influence of job satisfaction on performance. How influence competency, job culture and job satisfaction on performance. The purpose of this study to determine and analyze the effect of competency on performance. Determine and analyze the effect of job culture on performance. Determine and analyze the effect of job satisfaction on performance. Determine and analyze the effect of competency, job culture and job satisfaction on performance. Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate competency variable has a positive and significant effect on performance. Job culture variable has a positive and significant effect on performance. Job satisfaction variable has a positive and significant effect on performance. Competency, job culture and job satisfaction variable has a positive and significant effect on performance.